Proteolysis in Caenorhabditis elegans sex determination: cleavage of TRA-2A by TRA-3 - Sokol, Sharon B. (Cold Spring Harbor Laboratory Press, 2000)
The Caenorhabditis elegans tra-3 gene promotes female development in XX hermaphrodites and encodes an atypical calpain regulatory protease lacking calcium-binding EF hands. We report that despite the absence of EF hands, TRA-3 has calcium-dependent proteolytic activity and its proteolytic domain is essential for in vivo function. We show that the membrane protein TRA-2A, which promotes XX female development by repressing the masculinizing protein FEM-3, is a TRA-3 substrate. Cleavage of TRA-2A by TRA-3 generates a peptide predicted to have feminizing activity. These results indicate that proteolysis regulated by calcium may control some aspects of sexual cell fate in C. elegans.